The first record of 4 species of monogenean flatworm on catfish (Clarias fuscus, Hemibagrus spilopterus and Pangasius macronema) in the Dak Lak, Vietnam - Quang Sang, Tran; Thanh Huyen, Tran Thi; Thuy Binh, Dang (Vietnam Journal of Biotechnology, 2021)
Catfish (Order Siluriformes) is one of the largest orders of teleosts containing about 4,100 species with with highly diverse and distributed worldwide, representing about 12% of all teleosts and ∼6.3% of all vertebrates. Catfish are of economic and ecological importance; many large fish species are raised or caught for food, and small fish are cultured as ornamental. Like other fish species, monogenean is a common ectoparasites on catfish with more than 379 species recorded. The current study collected 77 individuals of three catfish species, including Hong Kong catfish Clarias fuscus (n = 21), black spotted catfish Hemibagrus spilopterus (n = 17) and long barbels pangasiid catfish Pangasius macronema (n = 39)) in Dak Lak in 2016 - 2017. Based on morphological and genetic (18S rRNA gene) characters, this study recorded four new dactogyrid monogenean species on the hosts and in Vietnam, in which, Thaparocleidus armillatus and Mizelleus siamensis on P. macronema; Bychowskyella tchangi on C. fuscus, and Cornudiscoides longicirrus on H. spilopterus. Phylogenetic tree constructed of four 18S rRNA sequences from the current study and six sequences on Genbank showed Bychowskyella spp. species formed monophyletic clusters and is sisterly related to the remaining of the species. C. longicirrus species was clustered in the separate clade, while M. siamensis species exhibited paraphyly when grouped with species of the genus Thaparocleidus. There is a need for further analysis of taxonomic characteristics and molecular markers diversity (e.g. Cytochrome oxidase subunit (COI mtDNA), 16S rRNA) to determine the taxonomic position of monogenean species.